2014
DOI: 10.1007/s10457-014-9757-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of environment, land management, and spatial variables on recent changes in montado land cover in southern Portugal

Abstract: Abstract:Montado decline has been reported since the end of the nineteenth century in southern Portugal and increased markedly during the 1980s. Consensual reports in the literature suggest that this decline is due to a number of factors, such as environmental constraints, forest diseases, inappropriate management, and socioeconomic issues. An assessment on the pattern of montado distribution was conducted to reveal how the extent of land management, environmental variables, and spatial factors contributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 66 publications
2
84
2
Order By: Relevance
“…This agrees with our results, where short periods between clearings would inhibit the regeneration of trees, since mechanical clearing is a non-selective tool that destroys most seedlings (Arosa et al, 2015), thus the absence of immature trees directly affects negatively the population of adult trees. According to our long term results, we assume that extending shrub clearing for longer periods would benefit natural regeneration, which is in agreement with other short term studies (Canteiro et al, 2011;Godinho et al, 2014;Simões et al, 2016). In fact, other authors' conclusions suggest maintaining shrub cover for a period between 7 and 12 years to help cork oak regeneration and promote tree nursery and soil rehabilitation.…”
Section: Main Limitations To Regenerationsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees with our results, where short periods between clearings would inhibit the regeneration of trees, since mechanical clearing is a non-selective tool that destroys most seedlings (Arosa et al, 2015), thus the absence of immature trees directly affects negatively the population of adult trees. According to our long term results, we assume that extending shrub clearing for longer periods would benefit natural regeneration, which is in agreement with other short term studies (Canteiro et al, 2011;Godinho et al, 2014;Simões et al, 2016). In fact, other authors' conclusions suggest maintaining shrub cover for a period between 7 and 12 years to help cork oak regeneration and promote tree nursery and soil rehabilitation.…”
Section: Main Limitations To Regenerationsupporting
confidence: 92%
“…Furthermore, large-scale analyses are mandatory to fully understand the role of multi-scale cumulative drivers influencing the regeneration process and the role of policies in managing this ecosystem (Godinho et al, 2014). In this context, the combination of local population dynamics (temporal) and regional distributional (spatial) models can help to assess and predict how anthropogenic and environmental changes will affect the abundance and displacement of vulnerable species or communities in disturbed ecosystems and regions (Guisan and Thuiller, 2005).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Montado has a high proportion of semi-natural vegetation and supports rare species or a high proportion of European or world populations. These farm systems have been relatively stable over the last decades-no changes in the land management model were observed- (Godinho et al, 2016) and, thus, provide a suitable and proximate comparator from which to assess the impact of quarrying activities on local avifauna biodiversity.…”
Section: Study Areamentioning
confidence: 99%
“…Nuthall (2012) investigated the decision making process of farm managers and concluded that the rules and systems used by one farmer are not likely to apply to another due to their uniqueness. An assessment of montado area distribution revealed that land management, compared to environmental and spatial factors, accounted for more than 50 % of the montado area loss between 1990 and 2006 (Godinho et al 2014). Moreover management decisions in montados are also affected by the Common Agricultural Policy (CAP).…”
Section: Variable Decisions-anthropogenic Factorsmentioning
confidence: 99%